2018
DOI: 10.1098/rstb.2017.0078
|View full text |Cite
|
Sign up to set email alerts
|

Selective recognition of N 4-methylcytosine in DNA by engineered transcription-activator-like effectors

Abstract: The epigenetic DNA nucleobases 5-methylcytosine (5mC) and 4-methylcytosine (4mC) coexist in bacterial genomes and have important functions in host defence and transcription regulation. To better understand the individual biological roles of both methylated nucleobases, analytical strategies for distinguishing unmodified cytosine (C) from 4mC and 5mC are required. Transcription-activator-like effectors (TALEs) are programmable DNA-binding repeat proteins, which can be re-engineered for the direct detection of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 55 publications
0
31
0
Order By: Relevance
“…Gene-specific editing in vitro and in vivo is a hot topic, and the different methodologies available are compared by Rots [4]. One of these, the selective recognition of N4-methylcytosine by engineered transcription activators, is reported by Summerer [5]. While DNA is relatively faithful to the four Watson-Crick bases and variants are relatively rare, the opposite is true with non-coding RNAs, which rarely consist of only the canonical adenine, guanine, cytosine and uracil bases.…”
Section: What Is Heritable and What Is Not?mentioning
confidence: 99%
“…Gene-specific editing in vitro and in vivo is a hot topic, and the different methodologies available are compared by Rots [4]. One of these, the selective recognition of N4-methylcytosine by engineered transcription activators, is reported by Summerer [5]. While DNA is relatively faithful to the four Watson-Crick bases and variants are relatively rare, the opposite is true with non-coding RNAs, which rarely consist of only the canonical adenine, guanine, cytosine and uracil bases.…”
Section: What Is Heritable and What Is Not?mentioning
confidence: 99%
“…Dynamic DNA modifications, such as methylation and demethylation have an essential role in the regulation of gene expression. DNA methylation as a heritable epigenetic marker is one type of chemical modification of DNA, which alters genetic performance without altering the DNA sequence [ 1 , 2 ]. Several researches have shown that it has the ability to change DNA protein interactions, DNA conformation, DNA stability, and chromatin structure.…”
Section: Introductionmentioning
confidence: 99%
“…As an essential epigenetic modification, DNA base methylation expands the DNA content and plays crucial roles in regulating various cellular processes [ 1 3 ]. According to the location where a methylated group occurs in the DNA sequence, there are many kinds of DNA base methylation.…”
Section: Introductionmentioning
confidence: 99%